217k views
2 votes
How do I prove this equation?
* this is a grade 11 math problem.​

How do I prove this equation? * this is a grade 11 math problem.​-example-1
User Yawar
by
5.1k points

1 Answer

4 votes

Answer:

The answer to your question is below

Explanation:


(tan^(2) x)/(tan^(2) x + 1) = sin^(2) x


((sin^(2)x )/(cos^(2) x) )/((sin^(2)x )/(cos^(2) x) + 1) = sin^(2)x\\ convert tanx to sinx/cos x


((sin^(2)x )/(cos^(2) x) )/((sin^(2)x + cos^(2) x )/(cos^(2)x ) ) = sin^(2) x simplify


(sin^(2) x)/(sin^(2) x + cos^(2)x ) = sin^(2) x

sin²x + cos²x = 1 Use identity of sinx and cosx

sin²x = sin²x

User Jeverling
by
5.8k points